2016
DOI: 10.1021/acs.analchem.6b01141
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Doped Gold-Assisted Laser Desorption Ionization for Enhanced Imaging Mass Spectrometry of Triacylglycerols from Thin Tissue Sections

Abstract: The deposition of sodium salts followed by a sputtered layer of gold has been demonstrated to be a power combination for the analysis of triacylglycerols (TAGs) from tissue sections by laser desorption ionization (LDI) imaging mass spectrometry (IMS). Various sodium salts were tested for their capability to ionize TAGs and their ability to produce fast drying, small crystals (≤3 μm). The spray deposition of a sodium acetate and carbonate buffer mixture at pH 10.3 on which a 28 ± 3 nm sputtered layer of gold (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 36 publications
2
89
0
Order By: Relevance
“…Other lipids (e.g., phospholipids, sphingomyelin, fatty acids, etc.) also consistently formed silver-analyte adducts, and some species further fragmented in experiments by Muller et al 13 Sputtered gold has been utilized for ionization of cholesterol, 63 but this is only the second report of in solution AuNP sample preparation, giving an opportunity to further probe fundamental ionization effects. 64 It has now been shown that 20-nm AgNPs, 2-nm AuNPs, and 5-nm AuNPs effectively 4,32 Assuming that thermal heating plays an important role in the ionization mechanism, these differences in NP size give an opportunity to probe the potential zones of ionization.…”
Section: Resultsmentioning
confidence: 99%
“…Other lipids (e.g., phospholipids, sphingomyelin, fatty acids, etc.) also consistently formed silver-analyte adducts, and some species further fragmented in experiments by Muller et al 13 Sputtered gold has been utilized for ionization of cholesterol, 63 but this is only the second report of in solution AuNP sample preparation, giving an opportunity to further probe fundamental ionization effects. 64 It has now been shown that 20-nm AgNPs, 2-nm AuNPs, and 5-nm AuNPs effectively 4,32 Assuming that thermal heating plays an important role in the ionization mechanism, these differences in NP size give an opportunity to probe the potential zones of ionization.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in partial success, although some aggregation was apparent and caused signal loss, especially as the time between suspension preparation and spray deposition increased. An alternative to NP suspensions is the use of physical vapor deposition (PVD) (or sputter coating) to create NPs in situ, which has been demonstrated for Pt,, Au,, and Ag . We are currently working to compare several metal NPs produced via PVD for their efficacy in small molecule analysis.…”
Section: Development Of New Matrices For High‐spatial Resolution Imagingmentioning
confidence: 99%
“…Consistent with decreased expression of Scd1, analysis of the FA composition of liver using molecular profiling of tissue sections [22][23][24] by MS revealed a marked increase in saturated FA content of TG and phospholipids in HFAT compared to CD mice for Mthfr +/+ (Figure 6) as well as Mthfr +/− mice (Table S4, Supporting Information). This was also observed in another independent set of mice (data not shown).…”
Section: Oxidative Stress Scd1 Expression and Macrovesicular Steatosismentioning
confidence: 77%